On the Concept of Equity in Opportunity - Hyun H. Son (Asian Development Bank (ADB), 2011)
Measuring the equity of opportunity in a given society is an essential ingredient in the formulation of policies and programs that promote inclusive growth. In this paper, equity of opportunity is defined and measured through the theoretical framework of the social opportunity function, a concept similar to the social welfare function. The functional and graphical distribution of opportunity is discussed through the generalized Lorenz curve and the Bonferroni curve, while complete ranking of distributions is achieved through their related numerical indices: the concentration index and the Bonferroni index of opportunity, respectively. The concepts of relative and absolute measures of equity of opportunity are then introduced and a social opportunity index that considers both the amount and distribution of opportunity is developed. These measures are used to analyze changes in the opportunities for health care and education in the Philippines from 1998 to 2007.
hdl:11540/2017
Keywords: D63; I14; I15; I24; I25; I32; 330; Equity; Opportunity; Bonferroni Index; Concentration Index; Generalized Lorenz Curve; Education; Health; Soziale Wohlfahrtsfunktion; Neue politische Ökonomie